Diagnostic pitfall; interpretation of CA 19-9 concentrations in the presence of hepatic dysfunction. Issue 5 (May 1994) - Pearce, S; Thornes, H; Carr, D; Tanner, A
Abstract : A 50 year old man is described with hepatic dysfunction and chronic pancreatitis in whom greatly increased concentrations of the pancreatic tumour marker CA 19-9 combined with an abnormal appearance at endoscopic retrograde cholangiopancreatography lead to the false suspicion of pancreatic carcinoma. CA 19-9 concentrations should be interpreted with caution in patients with intrinsic liver disease or biliary obstruction.